Identification of Potential Virulence Factors in the Model Strain Acinetobacter baumannii A118 - Ramirez, Maria S.; Penwell, William F.; Traglia, German M.; Zimbler, Daniel L.; Gaddy, Jennifer A.; Nikolaidis, Nikolas; Arivett, Brock A.; Adams, Mark D.; Bonomo, Robert A.; Actis, Luis A.; Tolmasky, Marcelo E. (Frontiers in Microbiology, 2019)
Acinetobacter baumannii A118, a strain isolated from the blood of an infected patient, is naturally competent and unlike most clinical strains, is susceptible to a variety of different antibiotics including those usually used for selection in genetic manipulations. These characteristics make strain A118 a convenient model for genetic studies of A. baumannii. To identify potential virulence factors, its complete genome was analyzed and compared to other A. baumannii genomes. A. baumannii A118 includes gene clusters coding for the acinetobactin and baumannoferrin iron acquisition systems. Iron-regulated expression of the BauA outer membrane receptor for ferric-acinetobactin complexes was confirmed as well as the utilization of acinetobactin. A. baumannii A118 also possesses the feoABC genes, which code for the main bacterial ferrous uptake system. The functionality of baumannoferrin was suggested by the ability of A. baumannii A118 culture supernatants to cross feed an indicator BauA-deficient strain plated on iron-limiting media. A. baumannii A118 behaved as non-motile but included the csuA/BABCDE chaperone-usher pilus assembly operon and produced biofilms on polystyrene and glass surfaces. While a known capsular polysaccharide (K) locus was identified, the outer core polysaccharide (OC) locus, which belongs to group B, showed differences with available sequences. Our results show that despite being susceptible to most antibiotics, strain A118 conserves known virulence-related traits enhancing its value as model to study A. baumannii pathogenicity.